Endolumenal colon occlusion reduces peritoneal contamination during a transrectal NOTES procedure: a controlled porcine survival study - Senft, Jonas; Carstensen, Benedict; Mischnik, Alexander; Warschkow, René; Müller, Beat P.; Linke, Georg R. (Surgical endoscopy and other interventional techniques, 2016)
To enable an efficient and enduring decontamination of the rectal mucosa during transanal endosocopic procedures, we developed a device for reversible endolumenal colon occlusion (ColoShield). The aim of this study was to assess the value of ColoShield in reducing peritoneal contamination during a transrectal procedure.